1971
DOI: 10.1136/jcp.24.2.152
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and electron microscopic study of a calcifying epithelial odontogenic tumour

Abstract: SYNOPSISThe clinical features and the histological and ultrastructural appearances of a case of calcifying epithelial odontogenic tumour are described. The ultrastructural features of the cells of this tumour are comparable to cells of the stratum intermedium of the enamel organ. It is suggested that the amyloid-staining material found in this tumour is a cellular secretion rather than a cytoplasmic degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…It was earlier believed that CEOT originated from dental lamina, reduced enamel epithelium, or from the basal cells of the oral epithelium. It has also been proposed that CEOT arises from cells of the stratum intermedium of the dental organ by electron microscopic and histochemical evidence 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was earlier believed that CEOT originated from dental lamina, reduced enamel epithelium, or from the basal cells of the oral epithelium. It has also been proposed that CEOT arises from cells of the stratum intermedium of the dental organ by electron microscopic and histochemical evidence 6 …”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that CEOT arises from cells of the stratum intermedium of the dental organ by electron microscopic and histochemical evidence. 6 The incidence of CEOT varies between 0.4% and 3% of all odontogenic tumours. 5 CEOT can occur at any age; however, it is most often seen between 30 and 50 years of age, with no sex predilection.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme histochemical studies have revealed strong alkaline phosphatase activity in the tumor cells (7)(8)(9). The homogenous acellular materials have been variably described as either amyloid-like (10)(11)(12)(13)(14)(15)(16)(17)(18) or not amyloid (5)(6)(7)(19)(20)(21). Electron microscopic studies have detected fibrillar structures in the acellular material that differs from amyloid (22,7,20) and resemble epithelial fibrillar proteins such as keratin (19).…”
mentioning
confidence: 99%
“…They suggested that the 5 nm fine filaments represented basal lamina rather than amyloid, but could not exclude the possibility of the 11 nm fibrils being amyloid. Mainwaring et al (1971) also regarded the fibrils in CEOT as being smaller than classic amyloid fibrils. Chaudhry et al (1972) observed that they consisted of randomly oriented fibrillar material measuring from 5 nm-15 nm.…”
mentioning
confidence: 99%